Intestinal Immune Imbalance is an Alarm in the Development of IBD - Chunli Hu; Shengtao Liao; Lin Lv; Chuanfei Li; Zhechuan Mei (Mediators of Inflammation)
Immune regulation plays a crucial role in human health and disease. Inflammatory bowel disease (IBD) is a chronic relapse bowel disease with an increasing incidence worldwide. Clinical treatments for IBD are limited and inefficient. However, the pathogenesis of immune-mediated IBD remains unclear. This review describes the activation of innate and adaptive immune functions by intestinal immune cells to regulate intestinal immune balance and maintain intestinal mucosal integrity. Changes in susceptible genes, autophagy, energy metabolism, and other factors interact in a complex manner with the immune system, eventually leading to intestinal immune imbalance and the onset of IBD. These events indicate that intestinal immune imbalance is an alarm for IBD development, further opening new possibilities for the unprecedented development of immunotherapy for IBD.